Scintillation characteristics of annular beams propagating through atmospheric turbulence along a slanted path. (31st July 2015) - Chen, Hong; Ji, Xiaoling; Ji, Guangming; Zhang, Hao
Abstract: Scintillation characteristics of annular beams propagating through atmospheric turbulence along a slanted path are studied by using the numerical simulation method and some new results are obtained, which are explained in physical terms. It is found that, when the zenith angle is not large enough, the saturation phenomenon of the scintillation index never appears even if the propagation distance is large enough, which is quite different from the behavior for the horizontal propagation case. However, under the same condition (i.e. the zenith angle is not large enough), the on-axis scintillation index still approaches an asymptotical value, which increases as the zenith angle increases, and depends on the obscure ratio of annular beams. Furthermore, the relation of the on-axis scintillation index between annular beams and flat-topped beams is also examined in this paper. It is shown that their relation will change as the zenith angle changes.